Kinetic Study of Gas Formation in Styrofoam Pyrolysis Process - I Dewe Ketut Anom (The University of Mataram, 2021)
This research aims to study the reaction kinetics of gas formation in the pyrolysis of styrofoam waste. Pyrolysis of styrofoam waste without a catalyst takes place at a constant temperature of 180°C. In contrast, the pyrolysis of styrofoam waste by adding a zeolite catalyst took place at a constant temperature of 170°C. The amount of styrofoam waste used in this research sample is 200 grams, and the natural zeolite catalyst is 5 grams. Pyrolysis of styrofoam waste without using a catalyst form a gas at a constant temperature of 180°C, the kinetics of the reaction takes place on the zero-order. This result follows the Arrhenius equation K = Ae10617/RT with an activation energy value (Ea) of 1.27x103 kJ.mol-1. Pyrolysis of styrofoam waste by adding a zeolite catalyst to gas formation at a constant temperature of 170°C also takes place on the zero-order. The equation follows Arrhenius K= Ae4711,5/RT and the activation energy value (Ea) is 5.66x102 kJ.mol-1.